ETNOBOTANI TUMBUHAN OBAT DI DESA WAIMANGIT KECAMATAN AIRBUAYA KABUPATEN BURU - John F. Sahusilawane; Maya M.S. Puttileihalat; Ardi Latbual (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2023)
The use of natural plants with medicinal properties is one of the skills that has been rarely found; even in some places, it has only become wisdom by the local community. The utilization of local plants as a source of medicines is an alternative that can be developed, and medicinal plants can be a choice to treat various types of diseases. This study aimed to examine the ethnobotany of medicinal plants in Waimangit Village, Airbuaya District, Buru Regency. The method used is a semi-structured interview, direct observation, and documentation. The results showed 34 types of plants used as medicine by the people of Waimangit Village, which were obtained from the forest and yard. 11 parts of plants are used, including seeds, sap, roots, bark, stems, leaves, flowers, tubers, rhizomes, fruits, and all aspects of plants. The most widely used plant parts as traditional medicine are the leaves, and the least used is the fruit. There are nine ways to use medicinal plants: grated, rubbed, peeled, pasted, pounded, boiled, wrapped, kneaded, and crushed. However, the most commonly used is by boiling. The effect of using traditional medicine (herbs or herbs) is smaller than using artificial (modern) chemical drugs.